2016
DOI: 10.12965/jer.1632840.420
|View full text |Cite
|
Sign up to set email alerts
|

Simple X-ray versus ultrasonography examination in blunt chest trauma: effective tools of accurate diagnosis and considerations for rib fractures

Abstract: Simple radiography is the best diagnostic tool for rib fractures caused by chest trauma, but it has some limitations. Thus, other tools are also being used. The aims of this study were to investigate the effectiveness of ultrasonography (US) for identifying rib fractures and to identify influencing factors of its effectiveness. Between October 2003 and August 2007, 201 patients with blunt chest trauma were available to undergo chest radiographic and US examinations for diagnosis of rib fractures. The two modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Rib fracture is the most common form of chest injury that may result from falls, automobile accidents, or assaults. A simple chest posteroanterior and rib series is usually a sufficient diagnostic tool (Hurley et al, 2004); however, other methods like computed tomography and ultrasound sonography are occasionally used to verify the diagnosis (Hwang and Lee, 2016). The primary treatment goal for rib fracture is pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…Rib fracture is the most common form of chest injury that may result from falls, automobile accidents, or assaults. A simple chest posteroanterior and rib series is usually a sufficient diagnostic tool (Hurley et al, 2004); however, other methods like computed tomography and ultrasound sonography are occasionally used to verify the diagnosis (Hwang and Lee, 2016). The primary treatment goal for rib fracture is pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…Failed detection rates have been demonstrated to be in the vicinity of 30% to 50% and because of this the true incidence of rib fracture still remains unknown . Disclosure of rib fractures with plain film radiography is limited unless there is a definite displacement or an obvious step‐off noted at the fracture site, and costal cartilage fractures cannot be convincingly detected unless there is sufficient ossification at the region of injury . The technicalities of obtaining a projection can also compromise rib fracture diagnosis considering that fractures cannot be detected at certain respiratory intervals or at particular angles of X‐ray projection .…”
Section: Discussionmentioning
confidence: 99%
“…Although CT of the chest was not used in this case study, it has been suggested that its limitations in the evaluation of rib fracture include a low specificity in the setting of a higher radiation dose . A reason for this lower specificity involves its inability to examine each rib parallel to its long axis but using both axial and coronal images has shown to improve the overall detection rate of rib fracture .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rib fractures are clinically suspected in the presence of the related history of the patient, coughing, and localization of the pain with palpation and deep breathing [2]. Unfortunately, there are several limitations on the chest x-ray [4,5]. Costal cartilage fractures could be radiologically overlooked unless the densely calcified cartilage is broken [4].…”
Section: Introductionmentioning
confidence: 99%